(untitled) - Quéré, Yves (Australia, 1998)
This manual, which constitutes one of the courses offered to the students. After having all taken, in physics, a course in quantum mechanics and a course in statistical physics. It includes physics of materials. These optional courses supplement numerous other courses(Mathematics, computer science, mechanics, chemistry, biology, economic sciences and also philosophy, languages...)
Keywords: Materials science